Efektivitas Aroma Terapi Lavender terhadap Insomnia pada Lansia - Mindayani, Sri; Yardi, Finny Rohmatul; Putri, Arlen Lidya; Fadilla, Nadya (Jurnal Riset Hesti Medan, 2021)
Insomnia is a condition where it is difficult to initiate sleep, maintain sleep, and sleep that has not been refreshing for 1 month or more.  This study aims to determine whether lavender aroma therapy can effectively reduce insomnia in the elderly. The research design used is a literature study, by means of literature articles or comparing several articles.  Elderly research subjects who experience insomnia.  From the results of research, several articles indicate that before giving lavender aroma therapy, almost all of the elderly experienced poor sleep quality and after giving lavender aroma therapy almost all experienced an increase in sleep quality.  It is hoped that further research can pay attention to the level of aromatherapy giving in order to provide more effective results.